VD_FINDINFO 674 vom 20. September 2024 - VD Tribunal cantonal (2024)
CLASSEMENT DE LA PROCÉDURE, ESCROQUERIE, PARENTÉ, PERSONNE PROCHE | 110 al. 1 CP, 22 ad 146 CP, 319 al. 1 CPP (CH), 428 al. 2 let. a CPP (CH